Exploration of Critical Thinking of Trainee Students at Regional Teacher Training Center in Takeo Province, Cambodia - and Kaewurai Wareerat, Vong Sam Aun (Journal of Community Development Research (Humanities and Social Sciences); Vol 9 No 1 (2559): January - April 2016, 2016)
The purposes of this research were to: (1) examine and evaluate critical thinking of trainee students at the Regional Teacher Training Center (RTTC) in Takeo province, Cambodia and (2) identify whether the demographic factors had related to trainee students’ critical thinking. An exploratory research was employed in this study, and the Watson-Glaser Critical Thinking Appraisal (WGCTA) was used to collect the data. 101 trainee students in year I who had been being trained at RTTC for the academic year of 2013–2014 were selected as sample size and randomized by using Krejcie and Morgan table. Descriptive statistics (Mean and Standard Deviation), Pearson Correlation, and content analysis were used to analyze the data. The findings revealed that trainee students’ critical thinking was generally at low level (= 1.88, S.D. = 0.24). Considering the mean score of each element from the highest to the lowest, the findings also indicated that the highest mean score was the interpretation subscale  (= 2.56, S.D. = 0.67), respectively followed by deduction (= 2.55, S.D. = 0.58), evaluation of argument (= 2.31, S.D. = 0.54), recognition of assumption (= 2.27, S.D. = 0.53), and the lowest on inference (= 1.01, S.D. = 0.59). Concerning the demographic factors, the results indicated a majority of respondents was male (58.4%), most of them held associate degree (59.4%), and also was 21-25 years old (62.4%).  Sex was statistically related to trainee students’ critical thinking (r = -0.23), but age and education were not related.      These findings revealed herein lacking in preparation of trainee students for critical thinking skills considered as essential in daily’s life and workplace. Regarding this matter, the existing curriculum, particularly teaching and learning environment was in needs for further strengthening so that critical thinking can be enhanced.    Keywords: Critical Thinking, Demographic Factors, Teacher Trainee Students
Keywords: Critical Thinking, Demographic Factors, Teacher Trainee Students